Glutamine as sole nitrogen source prevents induction of nitrate transporter gene NRT2.4 and affects amino acid metabolism in Arabidopsis - Svietlova, Nataliia; Zhyr, Liza; Reichelt, Michael; Grabe, Veit; Mithöfer, Axel (Frontiers in Plant Science, 2024)
Plants assimilate inorganic nitrogen (N) to glutamine. Glutamine is the most abundant amino acid in most plant species, the N-supplying precursor of all N-containing compounds in the cell and the first organic nitrogen molecule formed from inorganic nitrogen taken up by the roots. In addition to its role in plant nutrition, glutamine most likely also has a function as a signaling molecule in the regulation of nitrogen metabolism. We investigated whether glutamine influences the high-affinity transporter system for nitrate uptake. Therefore, we analyzed the expression of the nitrate transporter NRT2.4, which is inducible by N deficiency, in Arabidopsis thaliana grown under different nitrogen starvation scenarios, comparing nitrate or glutamine as the sole nitrogen source. Using the reporter line ProNRT2.4:GFP and two independent knockout lines, nrt2.4-1 and nrt2.4-2, we analyzed gene expression and amino acid profiles. We showed that the regulation of NRT2.4 expression depends on available nitrogen in general, for example on glutamine as a nitrogen source, and not specifically on nitrate. In contrast to high nitrate concentrations, amino acid profiles changed to an accumulation of amino acids containing more than one nitrogen during growth in high glutamine concentrations, indicating a switch to nitrogen storage metabolism. Furthermore, we demonstrated that the nrt2.4-2 line shows unexpected effects on NRT2.5 gene expression and the amino acids profile in shoots under high glutamine supply conditions compared to Arabidopsis wild type and nrt2.4-1, suggesting non-NRT2.4-related metabolic consequences in this knockout line.